Application of printing defects detection based on visual saliency. Issue 1 (May 2021) - Zhang, Fuqian; Li, Yeli; Zeng, Qingtao; Lu, Likun
Abstract: Visual saliency means that when humans observe a certain area, humans automatically process the area of interest and selectively ignore the uninterested area. This local area is called the saliency area. In recent years, people have introduced image processing and pattern recognition detection methods based on visual saliency to simulate the biological visual attention mechanism, and achieved good results. This paper focuses on the process of printed product defect detection, analyzes the application of visual saliency in printed product detection in recent years, summarizes and compares the advantages and disadvantages of various printed product detection methods, and discusses future development trends.